FAKTOR-FAKTOR YANG MEMPENGARUHI EFISIENSI INVESTASI DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Aulia, Citra; elviani, sri; lubis, farida khairani; Simbolon, Ramadona (UNIVERSITAS DHARMAWANGSA, 2025)
This study was conducted to analyze the factors that affect investment efficiency with company size as an intervening variable in Food and Beverage sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The factors tested in this study include debt maturity, accounting conservatism, good corporate governance (GCG), and information asymmetry. Investment efficiency is important to determine a company's financial performance and ability to allocate capital optimally. This study uses a quantitative method with the Partial Least Square (PLS) approach to test the relationship between variables. Data were obtained from the company's annual financial report and processed using a statistical model to measure the direct and indirect influence of independent variables on investment efficiency through company size as a mediator. The results show that this study, (1) Investment efficiency is not affected by debt maturity, accounting conservatism, good corporate governance, and information asymmetry. (2) accounting conservatism and good corporate governance have a significant impact on company size, but debt maturity and information asymmetry do not affect company size (3) debt maturity, accounting conservatism, good corporate governance, and information asymmetry indirectly through company size function as intervening variables, do not have a significant effect on investment efficiency in Food and beverage companies listed on the Indonesia Stock Exchange.